Excellence or Misconduct: How the Visibility of Team Leaders Impacts the Research Project Competition in the Republic of Moldova? - Cuciureanu, G.; Turcan, N.; Cojocaru, Ir.; Cojocaru, Ig. (Science and Innovation, 2023)
Introduction. Distributing public funds to the “best” researchers is a key element of the science policy. Evaluation is a fundamental activity for the allocation of competitive funding. The flaws of peer review have led to increased interest in the use of bibliometric indicators for the evaluation of the research project proposals. Problem Statement. The advantajes and advance of bibliometrc is stimulated interest toward the correlation of peer review and applicants’ bibliometric indicators. The results of such studies are different and heterogeneous. Such studies are insufficient in Eastern Europe. Purpose. To establish the correlation between peer review and bibliometric indicators of project team leaders within the call for research projects in Moldova, which are financed from public funds for 2020—2023. Material and Methods. Statistical correlation of the results of national competition of R&D proposals (evaluation and funding) and the bibliometrics indicators of project team leaders (publications ant patents); analytical analysis of the contextual factors influencing this correlation. Results. The results of the analysis have shown a positive, albeit weak correlation between the scores assigned by experts and the previous performances of leaders. The most significant relation is between the call results and the Hirsh index in Web of Science and Scopus databases. However, the projects proposed by the most cited researchers in WoS and Scopus or the founders of scientific schools did not receive funding. Conclusions. The analysis of the national R&D competition has proved that previous scientific performance of team leaders influenced the evaluation results and the funding of project proposals. However, these dependencies are not linear and seem to be affected by the conflicts of interest and “old boys” schemes. This fact calls for significant changes of the process: ensuring the transparency, the involvement of foreign experts and the use of bibliometric indicators in evaluation.